2010
DOI: 10.4085/1062-6050-45.6.560
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Face-Mask Removal Effectiveness: A Comparison of Traditional and Nontraditional Football Helmet Face-Mask Attachment Systems

Abstract: Context: Football helmet face-mask attachment design changes might affect the effectiveness of face-mask removal.Objective: To compare the efficiency of face-mask removal between newly designed and traditional football helmets.Design: Controlled laboratory study. Setting: Applied biomechanics laboratory. Participants: Twenty-five certified athletic trainers. Intervention(s):The independent variable was face-mask attachment system on 5 levels: (1) Revolution IQ with Quick Release (QR), (2) Revolution IQ with Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 9 publications
(46 reference statements)
0
28
1
Order By: Relevance
“…The full quick-release face mask in both helmet styles allowed for faster removal times than previously reported for helmets with only partial quick-release capability removed from a healthy model. 8,9 Toler et al 9 found that removal of a partial quick-release-style face mask took approximately 50 seconds, whereas Swartz et al 8 noted that removal times were around 33 seconds with the same style. Clearly, the superior face-mask design that allowed the greatest removal speed in our study was the ION 4D helmet, taking only around 20 seconds for complete removal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The full quick-release face mask in both helmet styles allowed for faster removal times than previously reported for helmets with only partial quick-release capability removed from a healthy model. 8,9 Toler et al 9 found that removal of a partial quick-release-style face mask took approximately 50 seconds, whereas Swartz et al 8 noted that removal times were around 33 seconds with the same style. Clearly, the superior face-mask design that allowed the greatest removal speed in our study was the ION 4D helmet, taking only around 20 seconds for complete removal.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11 Using an a level of .05 and power of 0.8, we determined that a sample of 24 participants (12 pairs) would be needed to demonstrate a large effect. Given that we were exploring equipment that had not been studied, we recruited a conservative sample of 40 participants (20 pairs; 21 men, 19 women; age ¼ 33.7 6 11.2 years, height ¼ 173.1 6 9.2 cm, mass ¼ 80.7 6 17.1 kg, professional AT experience ¼ 10.6 6 10.4 years), and 100% of participants completed the study.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Given the inherent challenges of face-mask removal, clinicians must be aware of the advancements that have occurred with respect to face-mask attachment systems. 7,10,18 One advancement in 2002 involved a spring-loaded mechanism nut-and-bolt system that secured the face-mask clip to the helmet. 7 Removal of the clip required a one-quarter turn with a flat-head screwdriver to release the clip from the face mask and helmet.…”
mentioning
confidence: 99%